Criminal Offender Trajectories and (White-Collar) Occupational Prestige - Piquero, Nicole Leeper (American journal of criminal justice, 2010)
Empirical research on criminal career offending patterns has identified distinct offender trajectories that exhibit substantial heterogeneity in both the size and shape of offending over the life course. Very little research however, has examined specific outcomes associated with offending trajectories. This study uses data from several hundred South London males who were part of the Cambridge Study in Delinquent Development to examine how offender trajectories through age 40 relate to job classification at age 48. Results indicate that high-rate chronic offenders are least likely to hold prestigious white-collar jobs, while non-offenders are the most likely to be in such positions. Directions for future research are highlighted.